(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
To ensure the reliability of accounting data and accounting statements, organizations are required to conduct an inventory of property and liabilities. During the inventory, not only the presence of property and liabilities, but also their condition and assessment are checked and documented.